Transaction Costs and Asset Prices: A Dynamic Equilibrium model - Vayanos, Dimitri (Review of Financial Studies, 1998)
In this article we study the effects of transaction costs on asset prices. We assume an overlapping generations economy with a riskless, liquid bond, and many risky stocks carrying proportional transaction costs. We obtain stock prices and turnover in closed form. Surprisingly, a stock's price may increase in transaction costs, and a more frequently traded stock may be less adversely affected by an increase in transaction costs. Calculations based on the “marginal” investor overestimate the effects of transaction costs. For realistic parameter values, transaction costs have very small effects on stock prices but large effects on turnover.